The Effect of Workload on Burnout with Role Stress as a Mediation Variable - sulastri; Putri Wahyuni (Human Resource Management Studies, 2021)
The purpose of this research is to analyze: (1) The effect of workload on burnout on nurse of DR.Drs. M. Hatta Hospital. (2) The effect of workload on role stress on nurse of DR.Drs. M. Hatta Hospital.(3)The effect of role stress on burnout on nurse of DR.Drs. M. Hatta Hospital. (4) The effect of workload on burnout of nurse on employees of DR.Drs. M. Hatta Hospital through role stress. The population in this study were all nurses of The DR.Drs. M. Hatta Hospital, totaling 124 people. The number of samples was determined using Slovin with the number of samples obtained as many as 94 people who were taken using proportional cluster random sampling.,. The analysis technique used is SEM analysis using smart PLS3. The result of this study is (1) workload has a positive effect on burnout in hospital nurses DR.Drs.M.Hatta Bukittinggi, (2) workload has a positive effect on role stress in hospital nurses DR.Drs.M.Hatta Bukittinggi , (3) role stress positive effect on burnout in hospital nurses DR.Drs.M.Hatta Bukittinggi, (4) Role Stress significantly mediates the relationship between workload and burnout in hospital nurses DR.Drs.M. Hatta Bukittinggi.